Response of Growth and Production of Shallots (Alium cepa L.) to Planting Spacing and Watering Time Eco Enzyme: - Lince Romauli Panataria; Meylin Saragih; Efbertias Sitorus; Pantas Simanjuntak; Lamria Sidauruk; Nobel; Ernitha Panjaitan (Jurnal Penelitian Pertanian Terapan, 2023)
This research was conducted on the land of UPT Tanjung Selamat Main Seed Center, Deli Serdang, North Sumatra Province, with an elevation of Â±25 meters above sea level. This research was conducted from February to May 2022. The purpose of this study was to determine the exact spacing and timing of Eco Enzyme watering on the growth and production of shallots (Allium cepa L.). This study used a factorial randomized block design (RBD). Factor 1 is the spacing consisting of: J1=15cm x 15cm, J2=20cm x 15cm, J3=25cm x 15cm. Factor 2 namely: Eco Enzyme Watering Time consisting of: W1=1x1 day, W2=1x2 days, W3=1x3 days. The results of the study showed that the spacing treatment had a significant effect on shoot age, root length, tuber/sample diameter, and tuber/sample dry weight. From the results of the study it was also found that J2 and J3 had the fastest germination age (2.37 days) when compared to treatment J1 (2.67 days), the highest root length was in treatment J3 (14.92 cm) and the lowest was in treatment J1 (13.22 cm), diameter The largest tuber/sample was in treatment J3 (20.38 mm) and the lowest was in treatment J1 (18.11 mm) and the highest tuber/sample dry weight was in treatment J3 (66.68 g) and the smallest was in treatment J1 (52.06 g).